Avaliação da osteocondução do β-TCP em calvária de ratos: análise histológica e histométrica - Puttini, Igor de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Autogenous bone grafts are considered the gold standard in the literature, both for quality and quantity of newly formed bone are superior when compared to other grafts. However, autologous bone grafts have limitations such as the need for a second surgical site and pitch, increasing surgical morbidity; limited availability for large reconstructions and unpredictable resorption rate. This led researchers to consider as an alternative its association with biomaterials or just using these as bone substitutes. The aim of this study was to evaluate the osteoconductive calcium phosphate ceramic in critical size defects in rats' calvaria. 45 rats (Rattus norvegicus, Albinus, Wistar) adult male, weighing between 450 and 500g were used. A defect of 7 mm diameter was performed on the calvaria of each animal. The animals were divided into three groups according to the material filling the defect. They were: clot (CG), membrane clot (MCG) and calcium phosphate ceramic (TCPG). Euthanasia were performed within 7, 30 and 60 days. The specimens were fixed in10% formalin, processed and stained with HE. Statistical analysis were conducted by comparing the control group and the treated. The tests were conducted by GMC software used for statistical analysis in studies in health. The 7 and 30 days experimental did not exhibit statistical difference in newly formed bone area between the fillers tested (p>0,05), however, when the 60-day group were compared, TCPG group showed a statistically significant new bone formation when compared to CG and MCG (p>0,001). Thus, the results suggest that the tested material may be a potential alternative grafts

Os enxertos ósseos autógenos são considerados padrão ouro pela literatura, tanto pela qualidade como a quantidade do osso neoformado são superiores quando comparado aos demais enxertos. No entanto, o enxerto de osso autógeno possui limitações, como a necessidade de um segundo tempo e sítio cirúrgicos, aumentando a morbidade cirúrgica; limitada disponibilidade para grandes reconstruções e uma taxa de reabsorção imprevisível. Isto motivou pesquisadores a considerarem como alternativa sua associação com biomateriais ou apenas a utilização destes como substitutos ósseos. O objetivo do presente estudo foi avaliar a capacidade osteocondutora do β-Tricálcio Fosfato (β-TCP) em defeito de tamanho crítico em calvárias de ratos. foram utilizados 45 ratos (Rattus norvegicus, albinus, Wistar), machos, adultos, com peso corporal entre 450 e 500g. Um defeito de 7 mm de diâmetro foi realizado na calvária de cada animal. Os animais foram divididos em três grupos segundo o material de preenchimento do defeito. São eles: coágulo (GC), coágulo membrana (GCM) e cerâmica de fosfato de cálcio (TCPG). Nos grupos experimentais de 7 e 30 dias não foi possível observar diferença estatística entre a área de osso neoformado dos preenchimentos testados (p>0,05), contudo, quando comparado os grupos de 60 dias o grupo TCPG apresentou uma neoformação óssea estatisticamente significante quando comparado aos grupos GC e GCM (p<0,001). Sendo assim, os resultados sugerem que o material testado pode ser uma potencial alternativa em enxertos
Keywords: Cerâmica; Materiais biomédicos; Fosfatos de cálcio; Ceramics